Effect of the coughing technique during subcutaneous heparin injection on pain severity and individual satisfaction (Revista Latino-Americana de Enfermagem, 2023)
Regarding the article “Effect of the coughing technique during subcutaneous heparin injection on pain severity and individual satisfaction”, with DOI number: 10.1590/1518-8345.6504.3924, published in the Rev. Latino-Am. Enfermagem, 2023;31:e3924, page 1:Where was written:Derya Uzelli Yılmaz2Fatma Düzgün32 Bursa Uludağ University, Health Application and Research Center, Bursa, Turkey.3 İzmir Katip Çelebi University, Faculty of Health Sciences, Department of Nursing, İzmir, Turkey.Now read:Derya Uzelli Yılmaz3Fatma Düzgün22 Bursa Uludağ University, Health Application and Research Center, Bursa, Turkey. 3 İzmir Katip Çelebi University, Faculty of Health Sciences, Department of Nursing, İzmir, Turkey.